2018
DOI: 10.1021/acs.jpcc.8b07086
|View full text |Cite
|
Sign up to set email alerts
|

Achieving High Dehydrogenation Kinetics and Reversibility of LiBH4 by Adding Nanoporous h-BN to Destabilize LiH

Abstract: Lithium borohydride (LiBH 4 ) is a potential high-capacity hydrogen storage material but is limited by its high thermal stability and poor reversibility. Nanostructured hexagonal boron nitrides (h-BNs) with thin-layer (TL-BN) and nanoporous (NP-BN) structures have been prepared by treating h-BN in a hydrolysis process of LiBH 4 and then mixing with LiBH 4 by ball-milling to investigate their catalyzing effect on dehydrogenation and rehydrogenation. Nanostructured h-BN, in particular NP-BN, with an average pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 58 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…The surface-modified AlN is prepared by an alcoholysis reaction of LiBH 4 similar to our previous work (Scheme ). , To be specific, AlN (Aladdin, 99.5% 2.0 μm) and LiBH 4 (Aladdin, 95%) were mixed well with a mass ratio of 1:1 by grinding in an agate mortar. The mixture was removed to a high-pressure reactor for treatment under 4 MPa hydrogen at 300 °C for 2 h. After cooling down to room temperature, the powder was reacted with 20 mL alcohol in a glass beaker by an ultrasonic cleaner (40 kHz, 400 W) for 1 h until no bubble formed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The surface-modified AlN is prepared by an alcoholysis reaction of LiBH 4 similar to our previous work (Scheme ). , To be specific, AlN (Aladdin, 99.5% 2.0 μm) and LiBH 4 (Aladdin, 95%) were mixed well with a mass ratio of 1:1 by grinding in an agate mortar. The mixture was removed to a high-pressure reactor for treatment under 4 MPa hydrogen at 300 °C for 2 h. After cooling down to room temperature, the powder was reacted with 20 mL alcohol in a glass beaker by an ultrasonic cleaner (40 kHz, 400 W) for 1 h until no bubble formed.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, h-BN (hexagonal boron nitride) was composited with LiBH 4. The polarity of h-BN induces the formation of a B–H bond on the h-BN surface to destabilize LiBH 4. , Thus, higher and more stable reversible capacity is achieved due to the formation of lithium intercalation compound Li x BN between h-BN and LiH/LiBH 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, remarkable absorption/desorption properties have been achieved in LiBH 4 /BN composites, probably because of the enhancement of H 2 dissociation, H – diffusion, and Li + diffusion by nanoscale BN . Nanostructured BN addition has a stronger effect on the kinetics than the addition of pristine h-BN. , The addition of various nitride types to the LiNH 2 /LiH composite system showed that h-BN was effective to improve hydrogen-desorption kinetics, probably because of the enhancement of Li + diffusion across the LiNH 2 /LiH interface …”
Section: Introductionmentioning
confidence: 99%
“…15 Nanostructured BN addition has a stronger effect on the kinetics than the addition of pristine h-BN. 16,17 The addition of various nitride types to the LiNH 2 / LiH composite system showed that h-BN was effective to improve hydrogen-desorption kinetics, probably because of the enhancement of Li + diffusion across the LiNH 2 /LiH interface. 18 T h i s c o n t e n t i s In our previous study, LiAlH 4 /h-BN composites were synthesized by ball-milling and their hydrogen-desorption properties were investigated.…”
Section: Introductionmentioning
confidence: 99%